Clinical Characteristics and Prognosis of Anti-AChR Positive Myasthenia Gravis Combined With Anti-LRP4 or Anti-Titin Antibody - Chen, Yuping; Tao, Xiaoyong; Wang, Yan; Xu, Shengjie; Yang, Yanhua; Han, Jinming; Qiu, Feng (Frontiers in Neurology, 2022)
Objective This study aimed to summarize the clinical characteristics and prognosis of patients with anti- acetylcholine receptor (AChR) positive myasthenia gravis (MG) with a combination of anti-LRP4 or Titin antibodies. Methods A total of 188 patients with generalized MG before immunotherapy were retrospectively collected and then divided into three groups: single anti-AChR positive-MG (AChR-MG, 101 cases), anti-AChR combined with anti-low-density lipoprotein receptor-related protein four-positive MG (AChR+LRP4-MG, 29 cases), and anti-AChR combined with anti-Titin-positive MG (AChR+Titin-MG, 58 cases). Clinical manifestations, therapeutic responses to immunotherapy, and follow-up information were analyzed. Results Of the 188 seropositive MG patients, 29 (15.4%) were positive for both AChR and LRP4 antibodies, and 58 (30.9%) were positive for both AChR and Titin antibodies. The mean disease onset ages in the three groups were 47.41 ± 7.0, 49.81 ± 9.2, and 48.11 ± 6.5 years, respectively. AChR+LRP4-MG showed female predominance (27.6% were males and 72.4% were females), with mild overall clinical symptoms. The AChR+Titin-MG group showed shorter times for conversion to generalized MG (5.14 ± 0.0 months) than the AChR-MG group (11.69 ± 0.0 months) and the AChR+LRP4-MG group (13.08 ± 0.5 months; P < 0.001 in both cases). Furthermore, AChR+Titin-MG group had increased bulbar dysfunction, higher incidences of thymoma (32.8 vs. 19.8% and 3.4%, P=0.035), more severe quantitative MG scores, as assessed by both QMG scores [15.5 (11.75–22.5) vs. 13 (8–19), P = 0.005; and 9 (6–14) P < 0.001], and MG-ADL scores [10 (8–13) vs. 8 (5–13), P = 0.018; and 6 (4–8), P < 0.001]. Treatment for AChR+Titin-MG was largely dependent on corticosteroids and immunosuppressive agents (56.7 vs. 19.2% and 16.7%, p = 0.028). The rates of achieving s(MMS) or better within 2 years following immunotherapy in the three groups were 51.5, 62.1, and 51.7%, respectively (P = 0.581). Conclusion Clinical symptoms of anti-AChR positive MG combined with Titin antibody were more severe and progressed faster than those in the AChR + LRP4 and AChR groups. Regardless of antibody status, all patients responded well to immunotherapy and had relatively good prognoses.